Family Change in Global Perspective: How and Why Family Systems Change. Issue 3 (23rd May 2019) - Furstenberg, Frank F.
Abstract : Changes in family systems that have occurred over the past half century throughout the Western world are now spreading across the globe to nations that are experiencing economic development, technological change, and shifts in cultural beliefs. Traditional family systems are adapting in different ways to a series of conditions that forced shifts in all Western nations. In this article, I examine the causes and consequences of global family change, introducing a recently funded project using the Demographic and Health Surveys (DHS) and U.S. Census Bureau data to chart the pace and pattern of changes in marriage and family systems in low‐ and middle‐income nations.